Silica/Protein and Silica/Polysaccharide Interactions and Their Contributions to the Functional Properties of Derived Hybrid Wound Dressing Hydrogels - Monica Mesa; Natalia Y. Becerra (International Journal of Biomaterials)
Multifunctional and biocompatible hydrogels are on the focus of wound healing treatments. Protein and polysaccharides silica hybrids are interesting wound dressing alternatives. The objective of this review is to answer questions such as why silica for wound dressings reinforcement? What are the roles and contributions of silane precursors and silica on the functional properties of hydrogel wound dressings? The effects of tailoring the porous, morphological, and chemical characteristics of synthetic silicas on the bioactivity of hybrid wound dressings hydrogels are explored in the first part of the review. This is followed by a commented review of the mechanisms of silica/protein and silica/polysaccharide interactions and their impact on the barrier, scaffold, and delivery matrix functions of the derived hydrogels. Such information has important consequences for wound healing and paves the way to multidisciplinary researches on the production, processing, and biomedical application of this kind of hybrid materials.